2015
DOI: 10.1007/s00384-015-2341-4
|View full text |Cite
|
Sign up to set email alerts
|

Young age of onset colorectal cancers

Abstract: In our cohort, a family history of colorectal cancer, known hereditary colorectal cancer syndrome, and inflammatory bowel disease account for nearly half of all cases of young colorectal cancer. Prompt investigation of symptoms is essential in patients with Sporadic early-onset colorectal cancers, which appear to arise through the classical adenoma-to-carcinoma sequence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
17
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 13 publications
3
17
3
Order By: Relevance
“…In Scotland, population screening does not begin until the age of 50. In contrast with previous studies investigating yCRC [12,18], incidence of poorly differentiatedor high-gradehistology was not found to be overrepresented in our patient group. An Australian study concurs with this finding, putting this discrepancy down to the subjective nature of determining tumour grade across the world [2].…”
Section: Discussioncontrasting
confidence: 99%
“…In Scotland, population screening does not begin until the age of 50. In contrast with previous studies investigating yCRC [12,18], incidence of poorly differentiatedor high-gradehistology was not found to be overrepresented in our patient group. An Australian study concurs with this finding, putting this discrepancy down to the subjective nature of determining tumour grade across the world [2].…”
Section: Discussioncontrasting
confidence: 99%
“…An age of 50 years has been considered the cut-off for early- vs. late-onset CRC according to previous publications1127. The reason that CRC screening is recommended for people starting at age 50 years in Korea28, as well as in many other national guidelines293031, is because screening colonoscopy studies have shown a significantly increased risk of advanced neoplasms among people older than 50 years323334.…”
Section: Discussionmentioning
confidence: 99%
“…Though the early age of onset for CRC is thought to reflect an increased genetic predisposition, the majority appear to be sporadic [5, 6]. CRC in young adults associated with known hereditary conditions such as Lynch syndrome comprises a minor component (15–17%) [710], whilst a further subset of cases have a clear familial basis with no attributable genetic aetiology [11].…”
Section: Introductionmentioning
confidence: 99%